2008
DOI: 10.1007/s00128-008-9604-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cypermethrin on Some Developmental Stages of Drosophila melanogaster

Abstract: This study investigated the effects of cypermethrin, a synthetic pyrethroid, on some developmental features of Drosophila melanogaster. Before the experiment the lethal concentration of this insecticide was determined. Cypermethrin solution was applied to Drosophila melanogaster by means of nutrition, by adding it to the culture medium. In the control group no such substance was applied. Our aim was to find out whether any developmental toxic effects occur, and, if they do, during which stage, by observing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The results of the present study showed that kefir, yogurt, and milk reduced the number of adults in Drosophila , thereby impeding development. The observation of a decrease in the number of adults in Drosophila is usually a result of the application of toxic substances ( Karataş and Bahçeci 2009a , Karataş et al 2011a , Karataş et al 2011b , Keser and Karataş 2012 ). Hence, it was unexpected that foods that are nutritious and beneficial for humans had such negative effects on Drosophila that they could be considered toxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study showed that kefir, yogurt, and milk reduced the number of adults in Drosophila , thereby impeding development. The observation of a decrease in the number of adults in Drosophila is usually a result of the application of toxic substances ( Karataş and Bahçeci 2009a , Karataş et al 2011a , Karataş et al 2011b , Keser and Karataş 2012 ). Hence, it was unexpected that foods that are nutritious and beneficial for humans had such negative effects on Drosophila that they could be considered toxic.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that males are more sensitive to kefir and females are more sensitive to milk and yogurt. Indeed, there are a number of studies showing that different substances have different effects on Drosophila in females and males, affecting female or male development in different ways ( Alentorn 1987 , Davey et al 1989 , Karataş and Bahçeci 2009a , Karataş et al 2011ab , Keser and Karataş 2012 ). It has been stated that protein and carbohydrates in Drosophila have different effects on the reproductive characteristics of the sexes and that this is due to the difference between the sexes in terms of reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the healthy third instar larvae that had climbed up were also counted in the Petri dish. The number of eggs in the medium at the beginning was compared with the number of larvae that developed at the end of the experiment ( Karataş and Bahçeci 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…They were incubated for one day in order to egg laid and then the adult flies were removed. The eggs in culture mediums were counted under a dissection microscope [9].…”
Section: Methodsmentioning
confidence: 99%